PAULO FREIRE’S CRITICAL PEDAGOGY IN EDUCATIONAL TRANSFORMATION - Chalaune, Bhawan Singh (International Journal of Research -GRANTHAALAYAH, 2021)
Through critical analysis, the purpose of this article is to reflect critically on some of the key aspects of Paulo Freire’s critical pedagogy and its contribution to educational transformation. This study is based on critical interpretation and the concept of some key terms in particular. First, this article gives a glimpse into the background of critical thinking, the theoretical basis of Freire’s critical pedagogy, and his life experience. Similarly, Freire’s critical thinking on the banking education system, which hinders the development of learner’s creative thinking, is discussed. These include the role of oppression and dehumanization of the traditional and banking system of education, dialogue and conscientization, libations and problem-posing education, praxis as the reflection in the situations, the role of political and cultural factors in educational change. Second, based on Freire’s critical pedagogy, there is a critical interpretation of the current school system’s educational process, Practicing Freedom based Teaching Strategies, curriculum planning, and possible transformation into teacher and learner roles. Therefore, to prepare a citizen inspired by freedom and humanization, it is necessary for learners to have critical pedagogical method that can move forward by establishing a connection between themselves and their environment. This requires collaborative and interactive based policies and teaching. It is hoped that such a study will provide some impetus for the transformation of the existing state of education, and will benefit the qualitative development of education.